Historical occurrence of Antarctic icebergs within mercantile shipping routes and the exceptional events of the 1890s - Headland, Robert Keith; Hughes, Nicholas Edward; Wilkinson, Jeremy Paul (Journal of Glaciology, 2023)
A major consideration for maritime activity in the Southern Hemisphere is the northern limit of icebergs, or the Southern Ocean Limit Of Known Ice (SOLOKI). This analysis of historical reports of icebergs during Southern Hemisphere voyages from 1687 to 1933 provides a basis for examination of their geographical and chronological occurrence during ~250 years. The analyses use tabulated data from 742 voyages and other reports from many sources, some including first-person descriptions. While these data are dependent on icebergs being reported by mariners, as well as the variable frequency of voyages, they demonstrate distinct periods of exceptional frequency of icebergs occurring in certain localities, particularly the far South Atlantic. Based upon historical records the evidence suggests unprecedented numbers of icebergs were present in southern shipping channels in the 1890s. When these historical observations are combined with modern iceberg drift trajectories, their possible origin can be elucidated. Owing to the numbers of icebergs seen and their geographical spread, our results suggest that this was possibly the largest near-synchronous calvings in the last 300 years, and the northernmost extent of the SOLOKI.
Keywords: Sørishavet; glasiologi; isfjell

Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir (Journal of Glaciology, 2015)
In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; isfjell; teknologi

Gigantisk isfjell i Sør-Atlanteren - Orheim, Olav (Polarboken, 1992)
Keywords: Sørishavet; glasiologi; isfjell

Vil noen satse formuen på isfjelltauing i Sørishavet? - Orheim, Olav (Polarboken, 1982)
Keywords: Sørishavet; isfjell; logistikk

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

Field experiments on Antarctic tabular icebergs - Kristensen, Monica; Orheim, Olav; Wadhams, Peter (Polar Record, 1981)
Keywords: Sørishavet; glasiologi; is; isfjell; isshelf; kalv; kalving

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis

Hvorfor er de Antarktiske isfjell så store? - Orheim, Olav (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; glasiologi; innlandsis; isbreer; isfjell; isshelf; kalving; topografi

Isfjell kan brukes til overrisling - Haraldsen, Gunnar (Polarposten, 1972)
Keywords: Antarktis; isfjell; teknologi